APIP Capability and Local Financial Supervision in Corruption Prevention: An Islamic Economic Perspective in Jambi - Rahayu Rahayu; Sri Rahayu; Enggar DP Arum; Ilham Wahyudi (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to analyse the effect of Good Corporate Governance (GCG), Local Financial Management (LFM), and APIP Capability on Corruption Prevention in local governments of Jambi Province. Design/methodology/approach – The research employed a quantitative approach with a causalcomparative design. The population consisted of 12 local governments in Jambi Province, all included as research samples through a total sampling technique. Data were collected from secondary sources, including MCP KPK, SAKIP, SPBE, and APIP capability reports issued by BPKP for the period 2020– 2022. Statistical analysis was performed using multiple linear regression with SPSS 25. The measurement model was tested for validity and reliability, with all indicators showing loading factors > 0.70, AVE > 0.50, and CR > 0.70, indicating acceptable construct validity and reliability. Finding/Results – The results show that the model is significant overall (F-test p = 0.018) with an explanatory power of R² = 0.521, meaning 52.1% of corruption prevention is explained by GCG, LFM, and APIP capability. However, partial testing indicates that only APIP capability significantly influences corruption prevention (β = 11.027; p = 0.011), while GCG (β = 0.042; p = 0.895) and LFM (β = 0.183; p = 0.372) are not significant. Originality/Value – This study contributes to the literature by emphasizing the dominant role of internal government supervision (APIP) in preventing corruption at the regional level, where previous studies focused primarily on external anti-corruption institutions. The integration of agency theory and institutional theory highlights why internal monitoring mechanisms are more effective than normative governance frameworks in reducing corruption risks